Biological Treatability Studies of Tetrachloroethylene-Contaminated Soil - Tokunaga, Takashi; Nagafuchi, Yoshitaka; Hanashima, Masataka; Kitamori, Shigeji; Sera, Nobuyuki; Furukawa, Kensuke; Matsufuji, Yasushi (Journal of the Japan Society of Waste Management Experts, 1998)
The reductive dechlorination of tetrachloroethylene (PCE) was studied using glass columns packed with PCE-contaminated soil, to which enriched anaerobic dechlorinating bacteria were added together with wastewater from bean curd to act as electron donors. In batch experiments, ca. 35% of PCE in the soil and more than 88% of PCE in the void water were transformed to cis-1, 2-dichloro-ethylene (DCE) after 29 months. No complete dechlorination from PCE to ethylene was observed under these conditions. On the other hand, in semi-continuous column experiments using wood chips as electron donors, complete elimination of PCE from the soil was estimated to be achieved after 66 months. DCE was detected in all column effluent, which was further degraded by adding toluene and phenol as substrates for aerobic bacteria. Moreover, a genetically modified Pseudomonas strain was very effective to degrade the DCE derived from PCE.